Communication by Tandem Running in the Ant Genus Cardiocondyla - Edward O. Wilson (Psyche: A Journal of Entomology)
During field work in Puerto Rico in June,196o, the author had the opportunity to study a hitherto little known form of communication among worker ants. This behavior, which for convenience might be called tandem running, involves the movement outward from the nest of closely coupled tandem pairs, and it apparently functions as a substitute or trail-laying to recruit fellow workers to food sources. On Puerto Rico, tandem running was studied more fully in the species Cardiocondyla venustula Wheeler but was also observed in a second member of the genus, C. emeryi Forel.